Federated Autonomous Databases: Project Overview - PRABHAKAR, Satya (Institutional Knowledge at Singapore Management University, 1993)
The paper presents an overview of an ongoing research program, Federated Autonomous Databases, sponsored by Rome Laboratory (US Air Force) and conducted by Honeywell in collaboration with the University of Minnesota and Georgia Institute of Technology. This program is exploratory in nature and is aimed at understanding and solving, within the scope of the program definition, the problem of providing integrated access to distributed, heterogeneous and autonomous databases.